Efficacy of a novel antimicrobial peptide against periodontal pathogens in both planktonic and polymicrobial biofilm states. (1st October 2015) - Wang, Hong-Yan; Cheng, Jya-Wei; Yu, Hui-Yuan; Lin, Li; Chih, Ya-Han; Pan, Ya-Ping
Graphical abstract: Abstract: Streptococcus gordonii, Fusobacterium nucleatum and Porphyromonas gingivalis represent the early, middle and late colonizers of the bacterial accretion in dental plaque biofilms. These sessile communities constitute a protected mode of growth that promotes survival in a hostile environment. This study describes a novel and unrecognized role for a synthetic cationic antimicrobial peptide, Nal-P-113, which inhibits and kills periodontal bacteria in planktonic state, inhibits the formation of biofilms and eradicates polymicrobial biofilms. Nal-P-113 is also stable in saliva, serum and saline solution. At a concentration less than 320 μg/mL which is harmless to normal oral cells, Nal-P-113 can kill bacteria in planktonic state. At a concentration of antimicrobial peptide Nal-P-113 (1280 μg/mL) which only causes slight damages to normal oral cells is needed to kill bacteria in biofilm state. It is worth mentioning that this concentration of Nal-P-113 is harmless to rat oral mucosa compared to chlorhexidine. The mechanism of Nal-P-113 inhibiting and killing periodontal bacteria might rely on the abilities to permeabilize and/or to form pores within the cytoplasmic membranes, thus causes the death of bacteria. Here, we provided a novel and stable antimicrobial peptide with very low mammalian cytotoxicity, which can inhibit and kill periodontal bacteria in both planktonic and polymicrobial biofilm states. Statement of Significance: Nal-P-113 is a potent antimicrobial peptide with strong antimicrobial ability, improved deficiency compared with other antibacterial peptides, and remains stable in phosphate buffered saline, saliva, brain-heart infusion medium and bovine calf serum. Nal-P-113 exhibits a broad spectrum of bacteriocidal activity with excellent eradicating capability on oral pathogens and the respective biofilms. In this study, we used propidium iodide staining, scanning electron microscopy and transmission electron microscopy to confirm that Nal-P-113 can perforate plasmalemma thereby resulting in the death of oral pathogens and disintegrate the respective biofilms. Nal-P-113 also showed effective anti-plaque biofilms and cytotoxicity in the rat periodontitis model. No adverse effects can be observed on the gingivomucosa tissue. In short, the antimicrobial peptide Nal-P-113 presented to be an effective yet have low mammalian cytotoxicity agent with potential application in the clinic. This study provides a proof of concept in applying antimicrobial peptides in the clinical perspective.